2008
DOI: 10.1007/s11258-008-9437-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat increases germination of water-permeable seeds of obligate-seeding Darwinia species (Myrtaceae)

Abstract: We examined the response of seeds to heat in four geographically restricted and one widespread species of shrubby Darwinia from the fireprone region of southeastern Australia. These shrubs are killed by fire and rely on seed germination after a fire to maintain populations. We replicated the germination trials across several sites and several fruiting seasons for most species. Seeds had a high level of viability and were largely dispersed in a dormant state, except in D. glaucophylla, where seed dormancy varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…Moreover, litter removal can indirectly inhibit seedling recruitment by reducing soil moisture (Figure b). Moreover, the increase in soil temperature inhibits seedling recruitment by sharply decreasing seed vigor (Auld & Ooi, ; Avhad & Marchetti, ; Lombraña, Porceddu, Dettori, & Bacchetta, ), or accelerating seedlings death at early stage (Binder & Fielder, ; Harper & O'Reilly, ). Litter removal does not regulate seedling recruitment by affecting ST because ST did not increase in litter removal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, litter removal can indirectly inhibit seedling recruitment by reducing soil moisture (Figure b). Moreover, the increase in soil temperature inhibits seedling recruitment by sharply decreasing seed vigor (Auld & Ooi, ; Avhad & Marchetti, ; Lombraña, Porceddu, Dettori, & Bacchetta, ), or accelerating seedlings death at early stage (Binder & Fielder, ; Harper & O'Reilly, ). Litter removal does not regulate seedling recruitment by affecting ST because ST did not increase in litter removal treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The promotive effect of heat shock on the germination of hard-seeded (physically dormant) species is widely known, however, there are relatively few reports of positive responses to heat shock in species with PD e.g. some Apiaceae [ 14 ], Ericaceae [ 29 , 37 ], Haemodoraceae [ 24 , 45 ], Lamiaceae [ 29 ], Myrtaceae [ 68 ], Poaceae [ 41 ], Proteaceae [ 39 ] and Rutaceae [ 57 , 69 , 87 ]. In the present study, we found that heat shock was essential for germination of B .…”
Section: Discussionmentioning
confidence: 99%
“…Heat shock treatments were applied by placing seeds in aluminium foil cups and exposing them to 90°C in a pre-heated oven for 10 minutes. This temperature and duration of heating falls within the range of conditions experienced by seeds in the upper layers of the soil during the passage of fire [ 67 ], and has been reported to promote germination of a wide range of local species [ 27 , 68 ], including several Rutaceae [ 69 ]. Smoke treatments were applied by placing seeds in aluminium foil cups inside a 60 L plastic chamber and piping in aerosol smoke for 10 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…This range of optimal temperatures for final germination is not exclusive of C. ladanifer and is found in a variety of other species from fire-prone ecosystems [26,45,46,47,48,49,50] strongly suggesting that it represents what may be a generalized adaptive response to recurrent fires. However the discussion of whether it is in fact an adaptation or an exaptation [51,52,53,54] is beyond the scope of this paper.…”
Section: Discussionmentioning
confidence: 91%
“…Fire effects on soil are known to be extremely variable and heterogeneous either at soil surface or at deeper levels [36] and it has been suggested that lethal temperatures occur in soils during fires but generally confined to the soil surface [45,74]. To our knowledge no data exist on time-temperature distributions in soil during fires in C. ladanifer stands.…”
Section: Discussionmentioning
confidence: 99%